(untitled) (Experimental biology, 2019)
Osteoporosis is a progressive systemic skeletal disease characterized by reduced bone density and disrupted microarchitecture of the bone tissue that leads to increased bone fragility and elevated risk of bone fractures. In osteoporotic condition decrease in bone density and strength happens not only due to the increased osteoclastic activity but also due to the decreased number of osteoblast cells precursors (mesenchymal stem cells) and development of so called “osteogenic insufficiency”. We proposed the new method of cell therapy with adipose derived mesenchymal stem cells (AT-MSCs) and surface modification with synthetic bisphosphonate osteophilic polymer that would restore the osteoblast progenitor pool and at the same time inhibit osteoclastic activity in the regeneration zone of osteoporosis associated fractures. In current paper we have outlined the process of osteophilic polymer synthesis, isolation of homogenic population of AT-MSCs and assessment of the purity of obtained cell populations, assessment of polymer effect on cell proliferation and subsequent differentiation down the osteogenic lineage and polymer effect on the osteoclastic activity in vitro. According to the obtained data polymer was not found to be cytotoxic and did not affect the speed of MSCs proliferation. Surface modification with the polymer has no effect on cell osteogenic differentiation however inhibits phagocytic activity of bone marrow derived macrophages. Polymer functionalized MSCs could be subsequently used in further animal studies to assess the efficacy of suggested approach for stimulation of regenerative processes in vivo using the animal model of osteoporosis and osteoporosis associated fractures of compact bones. Keywords: osteoporosis, osteoclasts, reparative osteogenesis, adipose mesenchymal stem cells, osteophilic polymer, cell therapy.